Penerapan Purchasing Planning Dalam Pengadaan Bahan Baku Meubel Pada PT. Anugerah Putra Siantan - Magdalena Wilhelmina; ST. Salmia L.A; Soemanto Soemanto (Jurnal Valtech, 2021)
Purchasing planning need to do to determine future needs and determine the optimal re-order point. Based on data, there was a decreased arrival of wood raw material at PT. ANUGERAH PUTRA SIANTAN Singosari 2015 2019 amounting to 9,77%. By using the SWOT analysis consist of strength, weakness, opportunities, and threat can find out the solution in facing challenges and cope the weakness that will be collaborated with EOQ method which is one of the methods that used in determining the amount of optimal order and well scheduled purchasing planning to resolve the identified weaknesses of the SWOT method. Method of collecting data used questionnaire and processed by POMQM for Windows 3 and IBM SPSS Statistic 20. The reults obtain refer to re-order point data amounting to 207.167 unit with order per period 24 days per year in order to sped up the production process, maintain product quality so that can overcome competitors growth threat.